Prospective associations of cardiovascular disease with physical performance and disability : A longitudinal cohort study in the Osteoarthritis Initiative. - Soysal, PINAR; Veronese, N; Stubbs, B; Koyanagi, A; Noventa, V; Bolzetta, F; López-Sánchez, GF; Cester, A; SOYSAL, PINAR; Maggi, S; Jackson, SE; Loosemore, M; et al. (My University, 2019)
Background Literature regarding cardiovascular disease (CVD) and incident physical performance limitations and disability in older people is equivocal. Aims This study aimed to investigate whether CVD is longitudinally associated with incident physical performance limitations and disability in a large population-based sample. Methods This was an 8-year prospective study using data collected as part of the Osteoarthritis Initiative. Participants were community-dwelling adults with knee osteoarthritis or at high risk for this condition. Diagnosed CVD was self-reported. Physical performance was assessed with measures of chair stand time and gait speed, whereas disability was assessed with the Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC). Longitudinal associations between CVD and changes in physical performance tests (chair stand time and gait speed) and disability score were analyzed using generalized linear models with repeated measurements. Results The analyzed sample comprised 4796 adults (mean age 61.2 years, 58.5% female), of whom 313 people (6.5%) reported CVD at baseline. During 8 years of follow-up, after adjustment for 11 potential confounders measured at baseline, those with CVD experienced a worse profile in chair stand time over the 8-year follow-up period than those without CVD (p= 0.006). Conclusion In a cohort of middle-aged and older adults with knee osteoarthritis or at high risk for this condition those with CVD experienced a worse profile in chair stand time over the 8-year follow-up period than those without CVD; however, CVD was not significantly associated with an increased incidence of poor gait speed and disability over 8 years of followup. Importantly, no associations were observed when utilizing propensity score matching.
Keywords: Cardiovascular disease; Chair stand time; Gait Speed; Osteoarthritis; WOMAC